2020
DOI: 10.1021/jacs.0c10945
|View full text |Cite
|
Sign up to set email alerts
|

Boron Carbon Nitride Thin Films: From Disordered to Ordered Conjugated Ternary Materials

Abstract: We present an innovative method for the synthesis of boron carbon nitride thin film materials in a simple furnace setup, using commonly available solid precursors and relatively low temperature compared to previous attempts. The as-prepared structural and optical properties of thin films are tuned via the precursor content, leading to a sp 2 -conjugated boron nitride− carbon nitride mixed material, instead of the commonly reported boron nitride−graphene phase segregation, with tunable optical properties such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 49 publications
6
55
0
Order By: Relevance
“…The bulk and the nanowired film show similar optical properties with their absorption edges locating at 471 and 456 nm, respectively. Correspondingly, their optical band gaps are 2.52 and 2.58 eV as identified by the Kubelka-Munk method (Figure 2B), which is in good agreement with previous reports (Giusto et al, 2020a). At the same time, we measured the transmittance of these three kinds of g-C 3 N 4 films, and found that the g-C 3 N 4 film prepared by the mixture of melamine and urea is more opaque, which will be more conducive to light absorption (Supplementary Figure S5).…”
Section: Methodssupporting
confidence: 92%
“…The bulk and the nanowired film show similar optical properties with their absorption edges locating at 471 and 456 nm, respectively. Correspondingly, their optical band gaps are 2.52 and 2.58 eV as identified by the Kubelka-Munk method (Figure 2B), which is in good agreement with previous reports (Giusto et al, 2020a). At the same time, we measured the transmittance of these three kinds of g-C 3 N 4 films, and found that the g-C 3 N 4 film prepared by the mixture of melamine and urea is more opaque, which will be more conducive to light absorption (Supplementary Figure S5).…”
Section: Methodssupporting
confidence: 92%
“…Increasing the boron content in the melamine-boric acid solid precursor leads, via the higher boron content in the ternary thin films, to a blue shift of the absorption. [10] BCN materials are expected to have very high refractive index with high transparency in the visible range. [23] Therefore, our BCN thin films were characterized by variable angle spectroscopic ellipsometry (VASE) over a broader spectral range which allows for modeling the dispersion and absorption properties.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the boron content in the melamine‐boric acid solid precursor leads, via the higher boron content in the ternary thin films, to a blue shift of the absorption. [ 10 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As predicted by theoretical studies, [3,4] the electronic structure of hexagonal boron carbon nitride (B x C y N z ) depends on the composition and atomic arrangement of B, C, and N in the lattice. [5] B x C y N z were early synthesized by pyrolysis of precursors, [6,7] and are now typically synthesized by chemical vapor deposition (CVD), [2,8,9] which commonly lead to phase segregation of boron nitride and carbon domains. [3] These methods result in structures that lack the atomic precision necessary to fully control and reproduce the predicted properties.…”
mentioning
confidence: 99%